The Evolving Strategy of Californium-252 Neutron Intracavitary Brachytherapy in Treating Patients With Low-Lying T2 or T3 Rectal Adenocarcinoma: From Fixed to Individualized Regime With Intrarectal Peritumoral Injection of Amifostine - Xiong, Yanli; Shao, Li; Liu, Jia; Zhou, Qian; Li, Chongyi; Liao, Maojun; Zhang, Lei; Dai, Xiaoyan; Li, Mengxia; Lei, Xin (Frontiers in Oncology, 2021)
Purpose To retrospectively and comparatively evaluate the improvement of the efficacy and safety on the addition of 252Cf neutron intracavitary brachytherapy (ICBT), individualized or individualized with intrarectal peritumoral injection of amifostine (IPIA) to external-beam radiotherapy (EBRT) or concurrent chemo-EBRT in 314 patients with T2N0-1 or T3N0-1 low-lying rectal adenocarcinoma. Methods Phase I: from 2009 to 2011, 157 patients were treated with additional 252Cf neutron ICBT for four fixed fractions with a total dose of 40–45 Gy-eq during the EBRT. Phase II: from 2011 to 2013, 75 patients were treated with individualized neutron ICBT delivered for two to five fractions with a total dose of 26–45 Gy-eq according to the response of tumor after concurrent chemo-EBRT. Phase III: from 2013 to 2014, 82 patients were treated with individualized ICBT protected by pretreatment IPIA. Results The 4-year local control rates for the entire T2 and T3 patients were 69.4, 72.0, and 79.3%, while the 4-year overall survival rates were 63.1, 54.7, and 72.0% (P=0.08), and the 4-year disease-free survival rates were 55.4, 52.0, and 69.5% (P=0.053) in Phases I, II, and III, respectively. The late complication (LAC, ≥G2) rates were 33.8, 26.7, and 15.9%, respectively (P=0.012), and the serious LAC (≥G3) rates were 4.5, 4.2, and 0%, respectively, in Phases I, II, and III. Conclusion Concurrent chemo-EBRT combined with individualized 252Cf neutron ICBT protected by IPIA shows promising efficacy and safety in treating low-lying T2 and T3 rectal adenocarcinoma patients without surgery opportunity or willing.